Extensão universitária: mobilizadora de processos democráticos na gestão da educação - Sauer, Cátia Ruas Teixeira (2018)
This dissertation aims to verify to what extent the university extension at the University of Passo Fundo (UPF) collaborates with democratic processes in the management of education. For this, it is made a brief historical route of the university in the world and in Brazil until arriving at the community university - the University of Passo Fundo -, in particular, to university extension and to the education Management Policies Project: the effect, the necessary and the possible, with collaborates with the formation of educational space managers, linked to the Regional Education Center (Education University/UPF). Besides that, some concepts are reviewed, including, university, community university, education management and university extension, taking as reference the studies of Frantz (2011), Paro (2007), Freire (2013), among others. Use of the qualitative methodology, whose data were produced through the organization of a focal group. The discussions in the group involved the categories “two-way street”, “dialogue” and “territory”, which have been elaborated with a view to the contribution verification and analysis of university extension of the University of Passo Fundo as a mobilizer of educational management in educational spaces. Against the study carried out, it is verified that the university extension of the University of Passo Fundo represents a mobilizing and creative effect, in which educational managers in charge of different extensionist actions, like thematic rooms, pedagogical accessories, courses, forums, studies, publications, intertwine their experiences of everyday action with other formative experiences that allow to reflect and transform the management of education, in order to assume democratic processes in the professional conduct of their work. Their contributions also allow us to review and reflect on the conceptions of the role of university extension in contemporaneity.